AlxGaN1‐x/AlN/GaN and DH‐AlxGaN1‐X/GaN HEMTs Threshold Voltage Model. Issue 1 (31st October 2018) - Muhea, Wondwosen Eshetu; Kermas, Nawel; Yigletu, Fetene Mulugeta; Cabré, Roger; Iñiguez, Benjamin
Abstract : Physics based threshold voltage ( V th ) models for Alx GaN1‐x /AlN/GaN and double channel (DH‐Alx GaN1‐X ) HEMT devices are presented. Based on the concept that donor like surface states located on the AlGaN top are the source of electrons in the 2DEG, analytical Schottky barrier height ( ϕ b ) expression is derived and used in the development of the threshold voltage models. The calculated V th values for sample AlGaN/AlN/GaN and DH‐Alx GaN1‐X HEMT devices are consistent with the values extracted from published experimental data. Moreover, the V th models are incorporated in a recently proposed charge based I – V model for GaN HEMTs and DC characteristics of the devices under test are simulated. The model predictions are strongly correlated with experimental data in both the output and transfer characteristics cases over a full range of biasing conditions. Abstract : Physics based expressions for the Schottky barrier height ( ϕ b ) and threshold voltage ( V th ) of AlGaN/AlN/GAN and double channel AlGaN/GaN HEMT devices are derived. The models are implemented in a previous I – V model developed for GaN based HMETs, and excellent agreement is obtained between the experimental and model data.